2005
DOI: 10.17796/jcpd.29.3.kvu17822u2056508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the midpalatal suture during rapid palatal expansion in children: a CT study

Abstract: The midpalatal suture of 18 children submitted to rapid palatal expansion with the Haas fixed expander and ranging in age from 5 years 2 months to 10 years 5 months was evaluated with computerized tomography. The posterior nasal spine undergoes the impact of RPE in patients in the primary and mixed dentition stages, similarly to the anterior nasal spine though to a lesser extent. The average opening of the midpalatal suture was 2.21 mm in the anterior nasal spine region and 0.95 mm in the posterior nasal spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The anterior screw of the EDO was opened approximately 9 mm, causing a 60% orthopedic effect on the anterior region of the midpalatal suture (5.38 mm). The pattern of midpalatal suture opening observed for the EDO was similar to those described in previous studies with conventional RME expanders, 9,29 showing a triangular shape, as shown in Figure 1. Additionally, bone-tooth-borne expanders seem to produce a similar orthopedic effect compared with conventional Hyrax expanders.…”
Section: Main Findings In the Context Of The Existing Evidence And Insupporting
confidence: 86%
See 1 more Smart Citation
“…The anterior screw of the EDO was opened approximately 9 mm, causing a 60% orthopedic effect on the anterior region of the midpalatal suture (5.38 mm). The pattern of midpalatal suture opening observed for the EDO was similar to those described in previous studies with conventional RME expanders, 9,29 showing a triangular shape, as shown in Figure 1. Additionally, bone-tooth-borne expanders seem to produce a similar orthopedic effect compared with conventional Hyrax expanders.…”
Section: Main Findings In the Context Of The Existing Evidence And Insupporting
confidence: 86%
“…maxillary widths and the arch perimeter with a parallel-opening screw, centrally positioned in the palate. [6][7][8][9] Alternatively, the fan-type expander concentrates changes in the anterior region of the dental arch with negligible changes in the molar region. 10,11 Approximately one third of patients with maxillary constriction have a greater transversal deficiency in the intercanine width than the intermolar width.…”
mentioning
confidence: 99%
“…These values of suture expansion were similar to those found by some authors and different from others. 27,39,40 The differences could be mainly explained by different methods of investigation, times of examination after removing the appliances, and the age groups of the patients in each study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] The drawbacks of 2D cephalometry are distortion and magnification with poor reproducibility of landmark identification. [ 10 11 12 13 ] In order to avoid the inherit hitches of the 2D methods, 3D imaging based on computed tomography (CT) and cone-beam computed tomographic (CBCT) data were advocated;[ 14 15 16 17 18 19 20 21 ] however, there are certain limitations such as high cost, radiation dose, and artifacts created by metal objects. [ 22 23 ]…”
Section: Introductionmentioning
confidence: 99%